TEKNIK PEMBENTUKAN NOMINA DEVERBAL BAHASA INDONESIA DAN BAHASA ARAB (ANALISIS KONTRASTIF MORFOLOGI) - Yusri, Naelul; Aspahani, Aspahani; Ansori, Ansori (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2023)
This research examines the technique of forming Indonesian and Arabic deverbal nouns through contrastive analysis. The method used in this research is descriptive method with a synchronous time range. That is, the technique of forming Indonesian and Arabic deverbal nouns through a morphological derivation process will be described as is. The data will be taken from books and journals that study techniques for forming Indonesian deverbal nouns, and from sorof books that discuss techniques for forming Arabic deverbal nouns. The method that will be used by the author in contrasting the components of the two languages being compared is the comparative method. The results of the study show that the formation of Indonesian deverbal nouns uses the technique of derivational formor affixes and derivational compound affixes. The formation of Arabic deverbal nouns (masdar) uses several techniques: (1) sima'i technique (generally for masdar which is formed from fi'il sulation), (2) affixation techniques (preffix, infis, suffix, config), (3) changes in internal vowel sounds, (4) following certain wazn patterns and (5) using letter removal and letter replacement techniques. However, the essence of forming Arabic deverbal nouns is using the sima'i technique and following certain wazn patterns. As for whether or not the formation of Arabic deverbal nouns (masdar) is regular, some are formed regularly by following a special wazn pattern called the term qiyasi, and some are formed irregularly called the term goiru kiyasi, whose formation technique uses the sima'i technique.